Incorporating and embracing WIL component into career-based qualifications in traditional university education - Mokabe, M. (South African Journal of Higher Education, 2026)
The world of work continues to evolve, and there is growing recognition of the need for universities to adapt their education to the demands of the modern workplace. One promising approach is integrating Work-Integrated Learning (WIL) into career-based qualifications within traditional university education. This approach allows students to combine academic studies with practical work experience, enabling them to develop industry-relevant skills and knowledge while earning credits towards their degree. The qualitative study used thematic analysis. This article reviews the benefits and challenges of embracing WIL, including enhanced employability, improved student engagement, and increased graduate outcomes. The article also examines the challenges of implementing WIL, including ensuring quality assurance, managing logistics, and addressing equity and access concerns. Furthermore, the article explores future directions for WIL, including the potential for technology-enhanced WIL platforms, industry-academe partnerships, and the role of WIL in promoting lifelong learning and career development. By embracing WIL, universities can then better prepare students for success in a rapidly changing job market and contribute to the development of a skilled and adaptable workforce.